Climate change contributing to conflicts between livestock farming and guanaco conservation in central Chile: a subjective theories approach. Issue 2 (6th March 2021) - Vargas, Solange P.; Castro-Carrasco, Pablo J.; Rust, Niki A.; Riveros F., José Luis
Abstract: Negative interactions between guanacos Lama guanicoe and ranchers have recently intensified in central Chile because guanacos are perceived to be competing with livestock for pasture resources. We examined this conservation conflict with a novel approach that considers ranchers' subjective theories, to better understand the origins of the conflict and to identify effective conservation measures based on the participants' explanations. Our findings indicate that ranchers see the source of the current problem in a shift towards increasingly arid conditions associated with climate change. We suggest the ranchers' perceived problems are not only caused by interspecific resource competition arising from this climatic shift, but also by reported difficulties in negotiating with governmental institutions. This study adds to knowledge of human–wildlife interactions by exploring a further dimension of the complex ecological and social interactions taking place on livestock farms. We recommend identifying effective, acceptable solutions by considering and understanding the everyday knowledge of the conflict's protagonists and their potential for change.